THE COMPARISON OF THE USAGE OF GENDER CATEGORY IN PROVERBS IN UZBEK AND ENGLISH LANGUAGES - Satimova , Hayotkhon Karimovna (Educational Research in Universal Sciences, 2023)
Gender and language have become an interesting topic on which some linguists have done research to find out the relationship between them. Some of studies focus on the differences between language that is spoken by men and women in terms of phonology, syntax, and lexicon and conversation analysis. While the other studies have investigated the influence of gender-based differences on establishing and maintaining the imbalance power between the two genders. This paper will attempt to find out the relationship between gender and language and mentions briefly the main sociolinguistic approaches used in the study of gender and language. Besides that, the paper is going to discuss the impact of language on reproducing and reflecting social difference plus compares English and Uzbek phraseological units in terms of gender category. In addition, a case study in Uzbek is also mentioned to clarify the relationship between language and gender, followed by some implications for language planning at the end.